Relationship Between Working Periode and Using PPE with Hb Levels of Gas station Officers with Benzene Exposure in Cimahi City - Suhat Suhat; Gurdani Yogisutanti; Hadian Natawaluya; Linda Hotmaida (Jurnal Ilmu Lingkungan)
Gas stations have risks of benzene exposure. Benzene can cause anemia or decreased hemoglobin levels, due to the length of exposure, period of work, and use of Personal Protective Equipment. The purpose of this study to determine relationship between length of service and use of PPE on hemoglobin levels at gas station workers in Cimahi City. The study was conducted with a cross-sectional design on 100 participants from 10 gas stations. The working period was collected using a questionnaire, the use of PPE is measured by observation, and the measurement of hemoglobin levels is measured using an Hb meter instrument. The univariate statistical test uses frequency distribution and the bivariate uses the Spearman Rank Correlation. The results showed that 22% use PPE in the less category, 42% have worked for more than 5 years, and 35% of gas station workers in Cimahi City had low hemoglobin levels. The results of statistical analysis of the relationship between length of service and hemoglobin levels of gas station attendants in Cimahi City showed a value of p=0.001, and the relationship between the use of PPE and hemoglobin levels of gas station workers showed a value of p=0.390. The results showed that there was a significant relationship between length of service and Hb levels of gas station attendants, and there was no relationship between the use of PPE.